Ceasefire talks: What’s at stake for Ukraine’s agriculture sector and global food security? - Welsh, Caitlin; Dodd, Emma; Glauber, Joseph W. (Center for Strategic and International Studies, 2025)
More than three years following the launch of Russia’s full-scale invasion of Ukraine, Ukraine’s agriculture sector remains a primary target of Russia’s assaults. In attacking Ukraine’s agriculture sector, Russia seeks to diminish a major source of Ukraine’s revenue, undercut European support for Ukraine, and undermine Ukraine’s position as a global food exporter. At the same time, Russia has capitalized on Ukraine’s agricultural losses and the related increase in global food insecurity by increasing exports of its own grain to food-insecure countries. Proposed ceasefire plans would have significant implications for Ukraine’s and Russia’s agriculture sectors. As talk of a ceasefire continues, what is at stake for Ukraine’s agriculture sector, Russia’s agriculture sector, and global food security?